Developing Android-Based Bilingual E-Glossary for Civil Engineering Students - Aldino Putra Kurniawan (Jurnal Linguistik Terapan, 2020)
Vocational college students should constantly improve their proficiency so that they can compete in the working industry. One of many ways to improve is by utilizing their proficiency based on the theories which had been learned with the assistance from the relevant expert advisor. This project is the implementation. The purposes of this research project are (1) to develop a bilingual glossary of English for Civil Engineering presented in the android app; (2) to give appropriate solutions to the problems. In this research, there were five stages to develop the product: analysis, design, development, expert validation, and evaluation. The result of the research was a bilingual e-glossary application for Civil Engineering. The output of the research is beneficial for Civil Engineering Department students, people who study in the Civil Engineering field, and for D3 Program in Applied English at State Polytechnic of Malang.